Fostering Creative Self-Efficacy to Boost the Effect of Teaching Quality and Social Support on Creative Thinking of Vocational Students - Mahfud, Tuatul; Wu, Mingchang; Winnarko, Henry; Khieng, Channa (Journal of Technical Education and Training, 2024)
The acquisition of creative thinking skills is deemed essential for future employability. In the present setting, Vocational High Schools play a crucial role in equipping individuals with the necessary skills and fostering their creativity, thereby preparing them to become competent candidates for the workforce. Hence, it is necessary to foster creative thinking through the learning process by involving social support factors and the creative self-efficacy of vocational school students. This study examines the impact of teaching quality, social support, and creative self-efficacy on the development of creative thinking among vocational school students. This study is ex-post facto research. This study involved 342 vocational school students in the culinary arts field in the province of East Kalimantan, Indonesia. Data analysis in this study used structural equation modeling (SEM) via Amos 18 software. Study findings prove that social support and creative self-efficacy influence vocational school students’ creative thinking skills. Meanwhile, the teaching quality was proven not to influence the creative thinking skills of vocational school students significantly. Other findings of this study also reveal that creative self-efficacy as a mediator is influenced by the teaching quality and social support. Finally, this study showed that creative self-efficacy significantly mediated the effects of teaching quality and social support on vocational school students’ creative thinking skills. The results of this study provide important implications for vocational education practitioners to foster creative thinking skills through innovative teaching.